2015
DOI: 10.4238/2015.december.21.10
|View full text |Cite
|
Sign up to set email alerts
|

Critical genes in head and neck squamous cell carcinoma revealed by bioinformatic analysis of gene expression data

Abstract: ABSTRACT. In this study, bioinformatic analysis of gene expression data of head and neck squamous cell carcinoma (HNSCC) was performed to identify critical genes. Gene expression data of HNSCC were downloaded from the Cancer Genome Atlas (TCGA) and differentially expressed genes were determined through significance analysis of microarrays. Protein-protein interaction networks were constructed and used to identify hub genes. Functional enrichment analysis was performed with DAVID. Relevant microRNAs, transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Furthermore, MCM7 was proved as a potential biomarker in cervical cancers . And MCM7 is a tumorigenesis‐related gene, overexpression of MCM7 is common in multiple cancers like esophageal soft tissue sarcomas, head and neck squamous cell carcinoma and ESCC . Similar with our result, overexpression of MCM7 was also observed in colorectal cancer .…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, MCM7 was proved as a potential biomarker in cervical cancers . And MCM7 is a tumorigenesis‐related gene, overexpression of MCM7 is common in multiple cancers like esophageal soft tissue sarcomas, head and neck squamous cell carcinoma and ESCC . Similar with our result, overexpression of MCM7 was also observed in colorectal cancer .…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the role of 14-3-3γ in channel trafficking 30 , previous studies demonstrated the involvement of 14-3-3γ in tumorigenesis. 14-3-3γ has been shown to be one of key genes involved in osteosarcoma and head and neck squamous cell carcinoma 36 37 . Overexpression of 14-3-3γ has been reported in non-small cell lung cancer, promyelocytic leukemia and glioblastoma 38 39 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of therapy targets in tumors represents a challenge due to the presence of different cell types in the tumor microenvironment. Previous studies have attempted to look for targets in HPV+ and HPV− HNSCC without taking into consideration the complexity of the cell type composition of tumors [20]. These studies on bulk tumor may lead to both false positives and false negatives as the intercellular differences are confounded by differences in cellular composition.…”
Section: Introductionmentioning
confidence: 99%